Clinical and laboratory aspects of common variable immunodeficiency - Cristina M. Kokron (Anais da Academia Brasileira de Ciências, 2004)
Common variable immunodeficiency (CVID) is an immunological disorder characterized by defective antibodyproduction, recurrent infections, most notably of the respiratory tract, autoimmune phenomena andcancer. Some CVID patients may also present disturbances of the cellular immune response such as a decreasein the number and proportion of different lymphocyte populations, diminished lymphoproliferative responseto mitogens and antigens, altered production of cytokines, and deficient expression of cell-surface molecules.Most Brazilian CVID patients included in this study show a decrease in T and B lymphocyte counts in theperipheral blood. Furthermore, their lymphocytes are more susceptible to apoptosis following activation thannormal individuals, and they have a decrease in the expression of activation molecules like CD25, CD69,CD40L and CD70. Moreover, they show a decreased synthesis of IL-4 and IL-5 in comparison with normalindividuals. The increase in susceptibility to apoptosis following activation, may also be responsible for thedecrease in the expression of activation molecules and CD40L, decrease in Th2 cytokines synthesis, and inthe number of T and B circulating cells. In this study we discuss some of these immunological disturbancescorrelating them to the patients clinical features and comparing our patients findings to the literature.